Analysis of Waste Management and Greenhouse Gas Emission Reduction (Case Study: Adiwiyata School SMPN 18 Surabaya and Non-Adiwiyata School SMPN 31 Surabaya) - Bhakti, Wahyu Satria; Ni'am, Achmad Chusnun; Nurbia, Nurbia; Prasetyaningtyas, Dyan (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2024)
In Surabaya, a city program named